PELAKSANAAN PENYELIDIKAN TINDAK PIDANA PEMILU TAHUN 2019 OLEH KEPOLISIAN SELAKU PENEGAK HUKUM TERPADU (GAKKUMDU) DI SUMATERA BARAT - Joni Saputra dan Nurlinda Yenti (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
An integrated law enforcement center, or called Sentra Gakkumdu, is an effort to equalize understanding and patterns of handling election crimes among the Election Supervisory Body of the Republic of Indonesia, the National Police of the Republic of Indonesia and the Attorney General's Office of the Republic of Indonesia. Sentra Gakkumdu is regulated in Article 486 paragraph (1) of Law Number 07 of 2017 concerning General Elections to become a Law which states in paragraph (1):